1998
DOI: 10.1046/j.1365-2362.1998.00397.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth factor receptor expression in human gastroenteropancreatic neuroendocrine tumours

Abstract: In spite of the common cellular origin of these tumours, differences in growth factor receptor expression suggest the existence of different pathways during tumour subtype development.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
87
3
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(96 citation statements)
references
References 50 publications
5
87
3
1
Order By: Relevance
“…Only two studies have so far investigated c-Met expression in NE GI tumours. Wulbrand et al (1998) found the cMet mRNA expression frequencies to vary considerably, with the highest found in gastrinomas (33%) and the lowest (11%) in small intestine carcinoid tumours. In a gastrinoma study (Peghini et al, 2002), universal expression of c-Met mRNA was demonstrated in all 22 tumours investigated.…”
Section: Hgf- Egf-and Pacap-induced Proliferationmentioning
confidence: 97%
See 1 more Smart Citation
“…Only two studies have so far investigated c-Met expression in NE GI tumours. Wulbrand et al (1998) found the cMet mRNA expression frequencies to vary considerably, with the highest found in gastrinomas (33%) and the lowest (11%) in small intestine carcinoid tumours. In a gastrinoma study (Peghini et al, 2002), universal expression of c-Met mRNA was demonstrated in all 22 tumours investigated.…”
Section: Hgf- Egf-and Pacap-induced Proliferationmentioning
confidence: 97%
“…The EGF receptor is found (over)expressed in various human NE tumours (Nilsson et al, 1995;Wulbrand et al, 1998;Peghini et al, 2002), including GI carcinoids. More recently, the EGFR tyrosine kinase inhibitor gefitinib has been shown to inhibit growth of various NE GI tumour cells, including human carcinoid BON cells (Höpfner et al, 2003).…”
mentioning
confidence: 99%
“…It has been shown that BON1 cells and tissue specimens of SI-NETs express the transcripts of all three TGFβs (β1, β2 and β3) and both receptors (TGFβR1 and TGFβR2) (Beauchamp et al 1991, Chaudhry et al 1994, Wulbrand et al 1998, Wimmel et al 2003. The expression of TGFβ isoforms differs between tissue components with all three isoforms being present in tumour tissue, but only TGFβ2 showed strong IHC staining in stroma .…”
Section: Figurementioning
confidence: 99%
“…In vitro, FGF2 is shown to be expressed by BON1 cells and to stimulate proliferation of these cells (Beauchamp et al 1991). FGF receptors are found in most SI-NETs, both in tumour and stromal cells (Facco et al 1998, Wulbrand et al 1998. Although the presence of FGF2 in tumour cells and stroma suggests involvement in cellular processes of the TME, the effect of FGF2 on tumour development remains uncertain.…”
Section: Basic Fibroblast Growth Factor (Fgf2)mentioning
confidence: 99%
See 1 more Smart Citation